2002
DOI: 10.1093/humrep/17.7.1895
|View full text |Cite
|
Sign up to set email alerts
|

Hyperalgesia, nerve infiltration and nerve growth factor expression in deep adenomyotic nodules, peritoneal and ovarian endometriosis

Abstract: These results suggest a role of NGF in endometriotic pain and hyperalgesia in deep adenomyotic nodules. The strong expression of the NGF-TrkA pathway in deep adenomyotic nodules could explain why this type of lesion infiltrates in richly innervated anatomical sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
182
1
29

Year Published

2004
2004
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 280 publications
(232 citation statements)
references
References 24 publications
10
182
1
29
Order By: Relevance
“…It is likely that growth factors are involved in the coordinated reinnervation and vascularization of transplants (30,31) and may contribute to innervation of the ectopic endometrial growths. Thus, of relevance to ENDO in women, Anaf et al (7) found that nerve growth factor expression was greater in deeply infiltrating adenomyotic endometrial nodules when compared with other ectopic endometrial growths and that these nodules were located closer to nerve fibers.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…It is likely that growth factors are involved in the coordinated reinnervation and vascularization of transplants (30,31) and may contribute to innervation of the ectopic endometrial growths. Thus, of relevance to ENDO in women, Anaf et al (7) found that nerve growth factor expression was greater in deeply infiltrating adenomyotic endometrial nodules when compared with other ectopic endometrial growths and that these nodules were located closer to nerve fibers.…”
Section: Discussionmentioning
confidence: 97%
“…Another group used S-100 protein as a marker for nerve fibers to compare samples of deeply infiltrating adenomyotic endometrial growths with other growths. The percentage of patients complaining of pain was greater in women with adenomyotic growths than other growths, and the adenomyotic growths were more likely to infiltrate nerves (7). No study, however, has investigated whether the ectopic growths develop their own nerve supply.…”
mentioning
confidence: 99%
“…MCs are likely to sensitize primary nociceptive neurons by the release of nerve growth factor (NGF) and proinflammatory cytokines. Lesional NGF can, in turn, attract MCs and trigger their degranulation [24].…”
Section: Mast Cells In Ems: a Painful Liaison?mentioning
confidence: 99%
“…14,25 Endometrial cells then invade the epineurium and perineurium of the lumbosacral nerves. [3][4][5]25,40 Furthermore, studies examining endometriotic nociception have shown that endometrial cells possess considerable neurotropic properties, 26 secreting factors such as nerve growth factor, which stimulates neurite growth. Mechanisms allowing endometrial cells to migrate, adhere, and infiltrate nervous tissue are under investigation, but involve the complex interactions of integrins, cadherins, and matrix metalloproteinases.…”
Section: Discussionmentioning
confidence: 99%